Navigating challenges in human pluripotent stem cell-derived islet therapy for type 1 diabetes - Usama, Mohammed; Deng, Ying; Chen, Yiran; Milland, Théa; Malleshaiah, Mohan; Aghazadeh, Yasaman (Frontiers in Immunology, 2025)
In the past two decades, several tissues have been generated from the differentiation of human pluripotent stem cells (hPSCs) to model development or disease, and for use in drug testing and cell replacement therapies. A frontliner of hPSC-derived tissues used in cell replacement therapies are the pancreatic cells, which have entered multiple clinical trials since 2014 for the treatment of type 1 diabetes (T1D). Despite challenges in early trials, the detection of endogenous C-peptide in recipients was encouraging. The results and challenges of these trials inspired new areas of research, leading to incremental advances in cell differentiation and delivery technologies, and a deeper understanding of the transplantation microenvironment to enhance therapeutic efficacy and longevity. Reports from the most recent trials demonstrated success in reducing or eliminating exogenous insulin administration for people with T1D, increasing hope for a cure for T1D via regenerative medicine. Recent efforts can be broadly categorized into: (1) improving the cell product as surrogates of native beta cells, (2) promoting engraftment post-transplant to support cell survival, integration into the host, and endocrine function, and (3) developing immunomodulation strategies to reduce or circumvent immunosuppression regimen. In this review, we discuss recent and emerging advances in these three areas and the potential, risk, and scalability of experimental models to the clinic.